In silico Characterization of Poly (ethylene) Terephthalate (PET): Degrading Enzymes from Rhizobacter sp. for Enzymatic Degradation Mechanisms: Characterization of Rhizobacter sp. PET Hydrolases - Damuri, Nur Wahida; Mohd Rozdhi, Amira Azawani; Tirmizhi Abubakar, Munkaila; Wayan Gunam, Ida Bagus; Huyop, Fahrul; Oyewusi, Habeebat Adekilekun (Journal of Tropical Life Science, 2025)
Dienelactone hydrolase (DHL) from Rhizobacter sp. is an enzyme from the β‐ketoadipate pathway that belongs to the α/β hydrolase family. It involves the conversion of chloroaromatics, such as nitrophenols and hydrocarbons, into harmless metabolites. The sequence-based analysis of Dienelactone hydrolase from Rhizobacter sp. shows significant homology to the extensively studied polyethylene terephthalate hydrolase of Ideonella sakaiensis (IsPETase). IsPETase can degrade the polymer, polyethylene terephthalate (PET), at room temperature. It was chosen as a template for dienelactone hydrolase from Rhizobacter sp. that was studied as a putative PET hydrolase. This study employs bioinformatics tools such as Expasy Protparam, Clustal Omega, SWISS-MODEL, GROMACS and Autodock vina to analyse the amino acid sequence of this enzyme, predict its three-dimensional structure and study its binding interaction. The structure of the putative PET hydrolase has been determined with 0.9 GMQE value and an overall quality factor of 96%. The residues responsible in substrate binding interactions are Leu88, Ser160 and Trp185. Thus, this in silico analysis depicts the ability of the putative PET hydrolase to bind to the polymer polyethylene terephthalate.